GENERAL AND SPECIFIC FACTORS OF FUTURE ORIENTATION LINK TO AWARENESS OF MEANING IN LIFE - Koļesovs, Aleksandrs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Future orientation reflects individual orientation toward personal goals, including cognitive representations of these goals and goal-directed behavior. Recent meta-analytical studies confirmed the positive effects of future orientation in various life domains. The effect of goal-orientedness in developing meaning in life still needs to be explored. This study accounted for the variability of personal goals across the life span and socialization trajectories. It focused on the relationships between a complex factorial structure of future orientation and the presence of meaning in life in emerging adults acquiring tertiary education. In total, 555 students participated in the study (mean age was 21.13, SD = 2.45, 64% females). The Individual Future Orientation Scale and Meaning in Life Questionnaire were applied for measurement. The factor analysis demonstrated that the bifactor model of future orientation includes the general factor and additional specific factors of future-oriented behavior and family-related goals. The general future orientation and future-oriented behavior positively predicted the presence of meaning in life. The emphasis on future-oriented behavior in a complex prediction is in line with the significance of the purpose in life for subjective awareness of meaningful life.